Brantley, Jessica. 2022. Medieval English Manuscripts and Literary Forms. Philadelphia: University of Philadelphia Press. Pp. xiv + 346. ISBN 9780812253849. - Garrido, Edurne (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Book review of Brantley, Jessica. 2022. Medieval English Manuscripts and Literary Forms. Philadelphia: University of Philadelphia Press. Pp. xiv + 346. ISBN 9780812253849.